Web Service-Based Food and Beverage Ordering Application with Android Platform. Case Study: Rumah Makan Muslim Hajjah Zuleka - Fadiah Nurhani; Samsudin Samsudin (Budapest International Research and Critics University, 2022)
This research is intended to overcome the problems that exist in restaurants which require technology to solve these problems. The process of ordering food, recording and calculating incoming orders, as well as monthly transaction reports are still manual, this causes sluggishness in recording and serving food to customers, thereby losing some customers who are reluctant to wait, especially when the restaurant is busy. To improve service to customers, as well as make it easier for restaurants to manage transactions and reports, a platform was built that can help improve business, monitor data and restaurant management. This will bring customers, kitchens, cashiers, and managers together on a digital platform where customers can order food at the dining table. The kitchen can get orders right away and process them. Managers or cashiers can have all the data in one place to monitor and manage to be organized. Modeling the system using UML and the system will run on the apache server and in this system the web server and REST API are built using php, MySQL is used for database management. The android application for food and beverage ordering activities will be built with android studio using the Java programming language that communicates with the system server using the REST API. MySQL is used for database management. The android application for food and beverage ordering activities will be built with android studio using the Java programming language that communicates with the system server using the REST API. MySQL is used for database management. The android application for food and beverage ordering activities will be built with android studio using the Java programming language that communicates with the system server using the REST API.